A utilização dos recursos visuais e audiovisuais como ferramentas que auxiliam no processo de ensino/aprendizagem - Silva, Márcia Raquel Duarte da (2019)
This article aims to clarify and analyze questions about the use of visual and audiovisual resources in the practice of basic teaching in the early years as a pedagogical support. This qualitative research, using semi-structured interviews as a data collection tool, was conducted with four teachers from a Rio Grande do Norte State School Network, in addition to the use of literature analysis based on the proposed theme. Thus, this work is divided as follows: introducing about education with technology, including visual and audiovisual resources, in elementary school in the early years, painting the advancement of technologies and their arrival in the educational scenario, and later , addressing the teacher training required for the use of resources in the classroom and the challenges faced for such use in practice, being problematized through the speeches of the survey respondents. It was found that the appropriation of visual and audiovisual resources in the teaching practice by teachers can make the content dynamic, interactive and attractive, favoring a meaningful learning, considering the role that is played by the teacher through his teaching practice, the context in which teacher and student are inserted. The authors that supported this research were Rocha (1998), Polito (1997), Justino (2012), Moran (2013), Perrenoud (2000),